Transcending VUCA Challenges through the Development of Superior Human Resources for the Sustainability of Batik Madura - Arfy, Widya Rizka; Irawati, S Anugrahini; Wantara, Pribanus (Jurnal Studi Manajemen dan Bisnis, 2025)
In an era characterized by volatility, uncertainty, complexity, and ambiguity (VUCA), traditional industries such as Madura batik face tremendous challenges in maintaining their existence. Social transformation, technological advancements, and shifting market preferences demand rapid and strategic adaptation. This article discusses the importance of developing superior human resources (HR) as the key to sustaining the Madura batik industry in the face of VUCA dynamics. Using a qualitative-descriptive approach, this study explores local potential, skill development strategies, and strengthening of work character rooted in culture. Findings indicate that the sustainability of the Madura batik industry is strongly influenced by the ability of local artisans to address VUCA challenges, such as raw material price fluctuations, market preference shifts, limited access to technology, and insufficient contextual training. Synergy among artisan communities, educational institutions, government, and creative industries is required to foster a sustainable learning ecosystem. By building competent and competitive human resources, Madura batik has the potential not only to survive but also to thrive as a global cultural identity